APPLICATION OF GROUP GUIDANCE SERVICES WITH THE MAUIDZATUL HASANAH METHOD IN PREVENTING ONLINE LENDING BEHAVIOR IN ADOLESCENTS IN RIMBA ASAM - Wiguna, Muhammad Yudha; Suryati, Suryati; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2025)
This research is titled, "The Application of Group Guidance Services with the Mauidzatul Hasanah Method in Preventing Online Loan Behavior in Adolescents in the Acid Forest", In the modern era like today we are often spoiled with the development of technology that is so rapid and sophisticated, almost everything now is related to internet technology, for example, such as online buying and selling, online learning and even almost all transactions are done online,  The development of technology and the internet certainly has positive and negative effects on society and especially for young people, the purpose of this study is to find out what are the factors that cause someone to be trapped in online loans and how to apply group guidance services with the Mauidzatul Hasanah method in preventing online loans in adolescents in the forest of acid. The research method used in this study is qualitative, qualitative is carried out to observe objects in their natural conditions. The purpose of this research is to understand various phenomena experienced by the research subject, such as behavior, perception, motivation, action, and others holistically. All of this is explained descriptively using words and language in a specific natural context. Furthermore, for the data collection technique, the researcher conducted interviews with 10 research subjects, and the results of the study showed that before group guidance was carried out with the Mauidza Hasanah method to prevent online lending behavior, many teenagers in the Asam forest were not aware that consumptive behavior to follow mere lust and could be obtained by doing online lending had a bad impact on themselves and others. After being guided by the Mauidzatul Hasanah method, they slowly began to realize and did not do it again for their good. So it can be concluded that group guidance with the mauidza hasanah method can increase understanding, change the way of thinking and behaving for the better.